Physical ergonomics in peripheral nerve block - Mohd Fathil, Shahridan; Abd Ghani, Muhamad Rasydan; Chen, Kung-Yen; Lee, Pinhsin; Hou, Jin-De; Lin, Jui-An (MDPI, 2021)
The understanding of ergonomics is a vital competency for all peripheral nerve block operators. The essence of physical ergonomics for peripheral nerve block procedures can be summarised into three significant components: brain, musculoskeletal and needling. The first component includes strategies to optimise visuospatial neuroprocessing using equipment configuration. The second component reflects the careful planning of posture and position to improve procedural technique and reduce physical fatigue. The final component focuses on strategies to achieve needle beam alignment for optimal needle visualisation.